اللغة الاعلامية واللغة العربية... التأثير والتأثر واقع وآفاق - مليك, محمد (جامعة الوادي - University of Eloued, 2017)
يتمحور هذا المقال حول العلاقة الجدلية التي تربط اللغة الاعلامية باللغة العربية في التأثير والتأثر، ويسعى إلى معرفة مدى تأثر اللغة الاعلامية باللغة العربية وما مدى تأثير اللغة الإعلامية في اللغة العربية، وذلك في وسائل الاعلام الجماهيرية سيما الإذاعة والتلفزيون. This study is intended to address an important topic related to the media language and its relationship to Arab language; it also seeks to know the levels of influence of Arab language on the values of the media message, this study focused on radio and television as two more widespread means in the mass media.
مقال
Keywords: اللغة الإعلامية، اللغة العربية، التأثير، التأثر; Media language, Arab language, Impact